The Influence of Creative Thinking and Financial Literacy on Tax Compliance Intention with Nationalism as a Moderator - Wulandari, Retno; Tambun, Sihar; Putra, Rio Johan (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the effect of creative thinking and financial literacy on tax compliance intentions with nationalism as a moderating variable. This study was conducted on 115 respondents in DKI Jakarta, consisting of 93 women and 22 men with diverse educational backgrounds, the majority of whom were bachelor's degree graduates. The data were analyzed using descriptive statistical analysis, validity tests, reliability tests, and hypothesis tests through path models using SmartPLS 4.0. The results of the study indicate that creative thinking and financial literacy have a positive and significant effect on tax compliance intentions. Nationalism also has a positive and significant effect on tax compliance intentions, and is able to moderate the relationship between creative thinking and financial literacy with tax compliance intentions. The coefficient of determination shows that the research model can explain 67% of the variability of tax compliance intentions. Thus, nationalism strengthens the influence of exogenous variables on tax compliance intentions.